2007
DOI: 10.1111/j.1442-8903.2007.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of predator control operations at landscape scale

Abstract: Summary  Exotic predators are considered pests to wildlife and agriculture, requiring predator‐control programs. Effective monitoring of predator‐control operations is essential to justify their considerable cost, but often impossible in practice. The difficulties are especially severe if the target species is small and wide‐ranging, and the area to be protected is inaccessible and/or extensive. A convenient model predator of this type, the feral Ferret (Mustela furo), is subject to control on farmland in New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Other studies have shown some, but not general, improvements to native biota in the wake of livestock removal (Munro et al 2009, Lawley et al 2013. Generally, no reversal is possible to the conditions that prevailed pre-livestock grazing if original species have become locally extinct or have no chance to immigrate back, or in cases where physical thresholds such as soil degradation have been passed (Hobbs and Harris 2001, King et al 2007, Suding and Hobbs 2009). The chances for immigration of species that have been lost locally will depend strongly on dispersal strategy (e.g., many plants; Lawley et al 2013), or on size and mobility, as in many animals (Dickman 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown some, but not general, improvements to native biota in the wake of livestock removal (Munro et al 2009, Lawley et al 2013. Generally, no reversal is possible to the conditions that prevailed pre-livestock grazing if original species have become locally extinct or have no chance to immigrate back, or in cases where physical thresholds such as soil degradation have been passed (Hobbs and Harris 2001, King et al 2007, Suding and Hobbs 2009). The chances for immigration of species that have been lost locally will depend strongly on dispersal strategy (e.g., many plants; Lawley et al 2013), or on size and mobility, as in many animals (Dickman 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the three samples of stoats met this condition, probably because in New Zealand they maintain very large home ranges (often to >200 ha: King and Murphy 2005), but do not occupy all parts of them at once. The same applies to ferrets on pastoral farmland (King et al 2007a;King et al 2009). …”
Section: Interrogating Relative Density Indicesmentioning
confidence: 82%
“…Lastly, trials in areas with no recent history of pest control could test whether indices obtained from camera traps are sensitive to removal of known numbers of pest individuals (e.g. by shooting or trapping), as has been shown for ferrets (King et al 2007a).…”
Section: Discussionmentioning
confidence: 99%